The effect of amphetamine on regional cerebral blood flow during cognitive activation in schizophrenia - Daniel, DG (J Neurosci, 1991)
To explore the role of monoamines on cerebral function during specific prefrontal cognitive activation, we conducted a double-blind placebo- controlled crossover study of the effects of 0.25 mg/kg oral dextroamphetamine on regional cerebral blood flow (rCBF) as determined by 133Xe dynamic single-photon emission-computed tomography (SPECT) during performance of the Wisconsin Card Sorting Test (WCST) and a sensorimotor control task. Ten patients with chronic schizophrenia who had been stabilized for at least 6 weeks on 0.4 mg/kg haloperidol participated. Amphetamine produced a modest, nonsignificant, task- independent, global reduction in rCBF. However, the effect of amphetamine on task-dependent activation of rCBF (i.e., WCST minus control task) was striking. Whereas on placebo no significant activation of rCBF was seen during the WCST compared with the control task, on amphetamine significant activation of the left dorsolateral prefrontal cortex (DLPFC) occurred (p = 0.0006). Both the mean number of correct responses and the mean conceptual level increased (p less than 0.05) with amphetamine relative to placebo. In addition, with amphetamine, but not with placebo, a significant correlation (p = - 0.71; p less than 0.05) emerged between activation of DLPFC rCBF and performance of the WCST task. These findings are consistent with animal models in which mesocortical catecholaminergic activity modulates and enhances the signal-to-noise ratio of evoked cortical activity.